2019
DOI: 10.1002/mawe.201800109
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of reheated quenching temperature of 1000 MPa grade steel plate for hydropower station

Abstract: The strength and toughness of 1000 MPa grade steel plate for hydropower station treated by different reheated quenching temperatures were investigated. With the increasing of reheated quenching temperature, the yield strength and tensile strength increase sharply, whereas the value of impact toughness decreases slowly. The lath martensite with high density dislocations enhances dislocation strengthening. On the contrary, the acicular or block ferrite (soft phase) produced by intercritical quenching reduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Typical martensite with lath morphology can be observed in the outermost layer of the HAZ (layer I), as shown in Figure 3c. Generally, the prior austenite grains consist of several packets, which have the same habit plane, and the packets are composed of one or two blocks [22]. Moreover, many laths with low-angle grain boundaries exist within each block.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical martensite with lath morphology can be observed in the outermost layer of the HAZ (layer I), as shown in Figure 3c. Generally, the prior austenite grains consist of several packets, which have the same habit plane, and the packets are composed of one or two blocks [22]. Moreover, many laths with low-angle grain boundaries exist within each block.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…Therefore, the suitable bainitic microstructure with the improved ability of strain hardening contributes to the significant increase in GNDs at depths of ~0.6 mm and ~0.9 mm, as well as the elastic-plastic interface, which provides the space to allow the pile-up of GNDs. Furthermore, the accumulation of GNDs at the interface between the hard zone of lath martensite and the soft zone of ferrite + pearlite is generated to accommodate the strain gradient, producing forward stress in the hard zone and back stress in the soft zone, which together produce heterodeformation-induced strengthening and hardening that enhance the strength and ductility of the gradient-phased structure [22,40]. Moreover, it should be noted that the GND density distribution of the HAZ at depths of ~0.6 mm and ~0.9 mm (as Figure 8(d2,e2) show) is also significantly heterogeneous.…”
Section: Strength-ductility Mechanisms Of Gradient-phased Structurementioning
confidence: 99%
“…Besides the pretreatment state, the process parameter of intercritical quenching temperature also influenced the microstructural characteristics and governed the resulting mechanical properties. The results of the studies demonstrated that, with increasing intercritical temperature, the phase fraction of martensite was increased, which improved the strength but weakened the impact toughness [34,35].…”
Section: Introductionmentioning
confidence: 99%